Novel investigational drugs mimicking exercise for the treatment of cachexia. (2nd January 2016) - Penna, F.; Pin, F.; Ballarò, R.; Baccino, F.M.; Costelli, P.
Abstract : Introduction : Cachexia is a syndrome characterized by body weight loss, muscle wasting and metabolic abnormalities, that frequently complicates the management of people affected by chronic diseases. No effective therapy is actually available, although several drugs are under clinical evaluation. Altered energy metabolism markedly contributes to the pathogenesis of cachexia; it can be improved by exercise, which is able to both induce anabolism and inhibit catabolism. Areas covered : This review focuses on exercise mimetics and their potential inclusion in combined protocols to treat cachexia. The authors pay with particular reference to the cancer-associated cachexia. Expert opinion : Even though exercise improves muscle phenotype, most patients retain sedentary habits which are quite difficult to disrupt. Moreover, they frequently present with chronic fatigue and comorbidities that reduce exercise tolerance. For these reasons, drugs mimicking exercise could be beneficial to those who are unable to comply with the practice of physical activity. Since some exercise mimetics may exert serious side effects, further investigations should focus on treatments which maintain their effectiveness on muscle phenotype while remaining tolerable at the same time.